Preliminary Study of Emissions Regulation Effects on Future Commercial Aircraft Designs. - Romli, Fairuz Izzudin; Kamaruddin, Mohd Syahidie (2013)
Conventional aircraft designs have long beenhighly successful for commercial passengers transport markets.In recent years, there are researches carried out to explore afew revolutionary concepts such as the blended wing body.With expected stricter environmental regulations to be imposedby the aviation regulatory bodies for future flight operations,questions arise on the relevancy of conventional aircraft designsto remain competitive in years to come and on whether thesearch for new revolutionary aircraft designs has becomenecessary. This study aims to assess the situation by analyzingthe projected emission performance of conventional aircraftdesigns through changes of their parameters. Overall, theresults indicate that conventional aircraft designs face a toughchance to remain competitive when the proposed regulationtakes place and a more aerodynamically efficient design isnecessary.